Sala de recursos multifuncionais: um estudo de caso - Oliveira, Cassia Carolina Braz de [UNESP] (2016)
The current Education Policy establishes the Specialized Educational Services based on the implementation of Multifunctional Resource Classes (MRC), Type I and Type II. Many cities adopted the MRC as their main specialized education system, resulting in an increased number of enrollments of students with special needs in regular classes. In this context, this research was conducted to address the growing need to study the MRC; considering the complexity and amplitude of the theme, 14 questions were raised with the objective of studying the MRC as the locus of the Specialized Educational Services. The main objective of this research was to describe and analyze, using a set of questions proposed by the literature, the services offered in a MRC of a city in the state of São Paulo. The specific objectives were represented by the 14 questions, among which are questions that try to identify, analyze, describe and verify various aspects of the special education services such as the reasons that lead the city to implement MRC in its schools, the academic background of the specialist teacher, the school-family relationship and the contact between the specialist and the regular education teacher; and also specific questions about the strategies and resources used for teaching in the MRC. The research was based upon a Case Study, which is characterized by the definition based on pre-established criteria of the research unity. The research locus was an elementary school of the municipal education system of a city in the state of São Paulo. The instruments used for the data collection were structured interviews, observation schedules, the accessibility protocol and the Assistive Technology questionnaire. The participants were the local Special Education coordinating body, the specialist teacher, the regular teacher and the school board. Triangulation was used to analyze the data which was then organized in chapters according to the proposed objective. The results showed that the use of the 14 questions allowed for an extensive study of the MRC; they also showed, though, that it would be possible to elaborate new questions regarding, for instance, the socioeconomic indicators of the studied region, considering they had a considerable degree of influence over the study. The results also revealed a need to enunciate specific questions about the locus which will be studied, considering all the regional, cultural and economic differences that exist between different education systems. A necessity to dedicate some efforts towards preparing the special education teacher on how to correctly and efficiently handle the Assistive Technology, to define the resources and strategies backed by theoretical support, to strengthen the communication between the regular and the specialist teacher and between the school and the student’s family, and to enhance the accessibility policies were also observed by analyzing the results.